2011
DOI: 10.1007/s10800-011-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium chloride on corrosion of mild steel in CO2-saturated brines

Abstract: Corrosion rates of mild steel were measured in oxygen-free, CO 2 -saturated brines as a function of NaCl concentration employing electrochemical techniques. Decreased corrosion rates were observed as salt concentration increased. However, at high salt concentration (C20 wt% NaCl), corrosion rates were independent of the flow rate of CO 2 -saturated brine. To understand this phenomenon, corrosion surfaces were analyzed by scanning electron microscopy and X-ray diffraction and showed only residual iron carbide f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…The first observation can be explained by the "salting-out" effect of NaCl in reducing CO 2 solubility (Han et al, 2011a(Han et al, , 2011c: lower dissolved CO 2 at higher salt concentration leads to lower carbonic acid concentration and corrosion rate. The second observation (higher corrosion rate at pH 7-8 in higher salt concentration solution) reflects the increased bicarbonate concentration in the presence of higher salt concentration, resulting in higher corrosion rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first observation can be explained by the "salting-out" effect of NaCl in reducing CO 2 solubility (Han et al, 2011a(Han et al, , 2011c: lower dissolved CO 2 at higher salt concentration leads to lower carbonic acid concentration and corrosion rate. The second observation (higher corrosion rate at pH 7-8 in higher salt concentration solution) reflects the increased bicarbonate concentration in the presence of higher salt concentration, resulting in higher corrosion rate.…”
Section: Resultsmentioning
confidence: 99%
“…However, at pH 6-8, corrosion scale can develop in a few hours. Therefore, corrosion data for bare surface corrosion were collected once the corrosion rate and potential stabilized at around 20 min, long enough to reach steady state and short enough to avoid corrosion scale formation (Han et al, 2007(Han et al, , 2011c.…”
Section: Methodsmentioning
confidence: 99%
“…Much of this work has focused on carbonation of cement, including the studies of Kutchko et al (2007Kutchko et al ( , 2008Kutchko et al ( , 2009, Duguid and Scherer (2010), and the Schlumberger group (Barlet-Gouédard et al 2006, Rimmelé et al 2008, Fabbri et al 2009. Corrosion of steel in wellbore environments has received less attention, but includes experimental studies by Carey et al (2010) and Han et al (2011b).…”
Section: Other Recommendationsmentioning
confidence: 99%
“…Han et al also reported decreased corrosion rates with an increase of salt concentration from 0.5 to 20 wt. % (Han et al, 2011). They proposed a model showing that cathodic reactions were decelerated by NaCl but anodic reactions were not significantly affected.…”
Section: Introductionmentioning
confidence: 99%